Recent Developments in Minimally Invasive Cardiac Surgery: Evolution or Revolution?. (8th October 2015) - Marullo, Antonino G. M.; Irace, Francesco G.; Vitulli, Piergiusto; Peruzzi, Mariangela; Rose, David; D'Ascoli, Riccardo; Iaccarino, Alessandra; Pisani, Angelo; De Carlo, Carlotta; Mazzesi, Giuseppe; Barretta, Antonio; Greco, Ernesto
Abstract : Intraluminal aortic clamping has been achieved until now by means of a sophisticated device consisting of a three-lumen catheter named Endoclamp, which allows at the same time occlusion of the aorta, antegrade delivering of cardioplegia, and venting through the aortic root. This tool has shown important advantages allowing aortic occlusion and perfusate delivering without a direct contact with ascending aorta reducing meanwhile the risk of traumatic and/or iatrogenic injuries. Recently, a new device (Intraclude catheter) with the same characteristics and properties has been proposed and introduced in clinical practice. The aim of this paper is to investigate the differences between Endoclamp and Intraclude catheters and to analyze the advantages advocated by this new device for intraluminal aortic occlusion since it is noticeable as these new technological tools are gaining more and more attractiveness due to their appraised clinical efficacy.